( lo g x 2 ) 2 + lo g 1 5 = 1 + lo g 3 − lo g 2 , x = ?
Solve for positive real value of x .
Details and Assumptions :
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( l o g x 2 ) 2 + l o g 1 5 = 1 + l o g 3 − l o g 2
⇒ ( l o g x 2 ) 2 + l o g ( 3 ∗ 5 ) = 1 + l o g 3 − l o g 2
⇒ ( l o g x 2 ) 2 + l o g ( 3 ) + l o g 2 1 0 = 1 + l o g 3 − l o g 2
⇒ ( l o g x 2 ) 2 + l o g 3 + l o g 1 0 − l o g 2 = 1 + l o g 3 − l o g 2
⇒ ( l o g x 2 ) 2 + l o g 3 + 1 − l o g 2 = 1 + l o g 3 − l o g 2
⇒ ( l o g x 2 ) 2 = 0
x = 1
x can also be − 1 .
Log in to reply
But -1 is not the domain of Logarithm, I am right?
Log in to reply
If x = − 1 , then lo g x 2 = lo g ( − 1 ) 2 = lo g 1 = 0 . (Also, note that the LaTeX code for logarithm is \log.)
That is correct
Note that the problem says "positive real x". The more unusual part to me is that if you do not assume base 10, you get a complicated expression with domain (0,1) U [10,infinity)
Log in to reply
At the time I posted the comment above, the problem did not include the condition that x had to be positive. The problem has been edited since then.
Log in to reply
@Jon Haussmann – Oh I didn't realize that. Good job by you looking at how the problem is actually written instead of just going by "what usually happens"
A much easier solution would be this: Using the logarithm laws: LogMN = Log M + LogN and LogM/N = LogM - LogN, The equation can be simplified to log(15x^4) = 1 + log(3/2). Since 1 can be rewritten as log10, log(15x^4) = log10 + log(3/2) -> log(15x^4) = log(30/2) -> log15x^4 = log15, so 15x^4=15 -> x^4=1 -> x=1
Problem Loading...
Note Loading...
Set Loading...
(log x^2 )^2 + log 15 = 1 + log 3 - log 2
log x^4 + log 15 = log (10 * 3) / 2
log x^4 + log 15 = log 15
log x^4 = 0
x^4 = 10^0
x = 1